First SWARM Observations of the Artificial Ionospheric Plasma Disturbances and Field‐Aligned Currents Induced by the SURA Power HF Heating. Issue 22 (27th November 2019) - Lukianova, R.; Frolov, V.; Ryabov, A.
Abstract: A series of experiments were conducted with a conjunction between the midlatitude SURA ionospheric heating facility and the multisatellite SWARM mission. We present the first observations made by SWARM on the plasma perturbations and electric currents induced in the F 2 region ionosphere by the high‐power high‐frequency O‐mode radio wave pumping. In the heated region, significant effects include a localized increase of the electron temperature accompanied by stratification of the electron density and the magnetic signatures of field‐aligned currents (FACs). The spatial structure and amplitude of FACs indicate that the current system is likely associated with the unipolar diffusion and excitation of eddy electric currents in the ionosphere. Similar effects are revealed in the laboratory experiment but not previously observed in space. Key Points: SURA‐SWARM conjugate experiments First SWARM observations of HF heating over SURA are presented Plasma irregularities and eddy field‐aligned electric currents are detected by SWARM in the topside ionosphere